The Strategy of Arabic Learning for Inclusion Students in Islamic Primay School of Islamiyah Wathoniyah Jombang | Strategi Pembelajaran Bahasa Arab Bagi Siswa Inklusi di Madrasah Ibtidaiyah Islamiyah Wathoniyah Jombang - Mohamad Yahya Ashari; Rifatul Mahfudhoh (Mantiqu Tayr: Journal of Arabic Language, 2021)
This study pays close attention to explain the implemantation of inclusive education especially in using the strategies and its problems of learning process. The aims of this study are determinating of the learning objectives, strategy of arabic learning and the learning problems in arabic teaching for inclusion students in islamic primay school of Islamiyah Wathoniyah Jombang. This study uses the qualitative descriptive approach, it uses interviews, observation and documentation for collecting data. This study uses the method of data analisys by implementing the steps of Miles and Hubberman such as data colletion, data shorting, data display and conclusion. The results of this study are: 1) the subjects of arabic learning determinated to two subjects, they are the subjects of usual learning and the subjects of inclusive learning. 2) the arabic learning uses the strategy of contextual teaching and learning and the strategy of cooperative learning by applying language games and pictures. 3) the learning problems in arabic teaching are: (1) less effective of the time for arabic additional lessons outside of the official learning to increase the understanding of inclusion students, (2) the different varies of inclusion students caracteristicts, (3) the less communication and partipication of inclusion students parent.